2012
DOI: 10.1111/j.1461-0248.2012.01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting plant responses to mycorrhizae: integrating evolutionary history and plant traits

Abstract: We assessed whether (1) arbuscular mycorrhizal colonization of roots (RC) and/or plant responses to arbuscular mycorrhizae (MR) vary with plant phylogeny and (2) MR and RC can be more accurately predicted with a phylogenetic predictor relative to a null model and models with plant trait and taxonomic predictors. In a previous study, MR and RC of 95 grassland species were measured. We constructed a phylogeny for these species and found it explained variation in MR and RC. Next, we used multiple regressions to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 42 publications
6
105
1
Order By: Relevance
“…In addition, the lower fungal root colonization in the grass compared with the dicot species (Fig. 1), which is consistent with other studies 29 , may have contributed to the distinct response patterns observed. The differences in colonization levels may reflect contrasting strategies of nutrient acquisition 32 with the grass species allocating more in an extensive root system and the dicots investing more in symbiotic structures.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, the lower fungal root colonization in the grass compared with the dicot species (Fig. 1), which is consistent with other studies 29 , may have contributed to the distinct response patterns observed. The differences in colonization levels may reflect contrasting strategies of nutrient acquisition 32 with the grass species allocating more in an extensive root system and the dicots investing more in symbiotic structures.…”
Section: Discussionsupporting
confidence: 79%
“…This ancient origin of the symbiotic fungi allowed individual plant species to coevolve with the AMF from the corresponding plant speciation event on and to develop plant species-specific adaptations mirrored in specific metabolome changes under symbiosis, with this specificity being maintained, although the AMF associated with other plant species in parallel. In accordance, plant growth responses to AMF were described to be relatively open to evolutionary change with limited phylogenetic constraints 29 . Thus, metabolic modulation by AMF in one plant species only allows limited predictions for responses to the same fungal symbiont in another species.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, the overall weak response of "nutrient uptake structures" may be related to rather low nutrient inputs compared to other fertilization experiments (Treseder and Vitousek, 2001;Johnson et al, 2003;Wright et al, 2011). Additionally, the abundance of AMF was relatively low with average root colonization values of 25%, potentially indicating a low AMF dependency of plants in this system (Powell et al, 2009;Reinhart et al, 2012). Though we did not detect (treatment related) correlating factors clearly explaining the observed increase in soil aggregation, the repeated finding of these patterns at different sampling times substantiates the reported treatment effects.…”
Section: Discussionmentioning
confidence: 98%
“…However, these traits lacked a phylogenetic signal (K ( 1 for all traits), thus the phylogenetic clustering that we observed must result from unmeasured traits that are conserved. For example, root morphology or mycorrhizal fungal associations are generally clustered phylogenetically (Reinhart et al 2012, Chen et al 2013. Indeed, increased abundance of introduced plants in younger forests is often attributed to belowground interactions that might reflect such traits.…”
Section: Discussionmentioning
confidence: 99%